Is Performing Repetitions to Failure Less Important Than Volume for Muscle Hypertrophy and Strength?. Issue 5 (May 2020) - Lacerda, Lucas T.; Marra-Lopes, Rodrigo O.; Diniz, Rodrigo C.R.; Lima, Fernando V.; Rodrigues, Sara A.; Martins-Costa, Hugo C.; Bemben, Michael G.; Chagas, Mauro H.
Abstract : Abstract: Lacerda, LT, Marra-Lopes, RO, Diniz, RCR, Lima, FV, Rodrigues, SA, Martins-Costa, HC, Bemben, MG, and Chagas, MH. Is performing repetitions to failure less important than volume for muscle hypertrophy and strength? J Strength Cond Res 34(5): 1237–1248, 2020—The aim of this study was to investigate the effects of muscle failure (MF) or not to MF (NMF) training on strength and muscle hypertrophy relative gains (average and individual data). Ten men untrained in resistance training participated in the study. Each leg was allocated in 1 of 2 unilateral training protocols (MF or NMF with equal volume) on knee extension exercise. Both protocols were performed with 3–4 sets, 3 minutes' rest, and 55–60% of one repetition maximum (1RM). Rectus femoris and vastus lateralis muscles cross-sectional area (CSA), maximal muscle strength (1RM and maximal voluntary isometric contraction), and muscular endurance (maximum number of repetition) were assessed before and after 14 weeks. In addition, neuromuscular activation by normalized root mean square of the electromyographic signal (EMGRMS ) was measured in 2nd and 35th training sessions. The average results showed that both training protocols were similarly effective in inducing increases in strength and muscle hypertrophy gains. However, individual analysis data suggest that NMF protocol with equal volume may promote similar or even greater muscle hypertrophy (vastus lateralis) and muscular endurance performance when compared with MF protocol. Also, normalized EMGRMS responses analyzed during 2nd and 35th sessions were similar in MF and NMF protocols for rectus femoris and vastus lateralis muscles. In conclusion, MF and NMF protocol conducted with the same total repetition numbers produced similar maximal muscle strength performance and neuromuscular activation. Nevertheless, NMF training could be a more appropriate strategy to increase muscle hypertrophy (vastus lateralis) and muscular endurance performance in untrained individuals when compared with MF.